Application of Maqasid al-Shariah in managing mosque funds: a case study of Tabung masjid in Terengganu, Malaysia - Zakariyah, Luqman (University of Sharjah, 2016)
Mosque funds in Muslim countries where Tabarru‘āt (donations) operates should have had an enormous impact on Muslim empowerment and poverty alleviation.